Investigation of the swirl effect on CAMPRO 1.6L engine using GT-SUITE - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur (2009)
CAMPRO engine is a basic Double Overhead Camshaft (DOHC) which has a capacity of 1597 cc and installed with a total of 16 valves developed by Malaysian car manufacturer PROTON. The name CAMPRO is derived from its key design feature of the CAM PROFILE. Despite the low fuel consumption and good torque distribution, the engine still requires a lot of improvement to be made. That is why the CPS (Cam Profile Switching) is incorporated in the newer model of the CAMPRO as a solution to the previous CAMPRO problems.